Pendekatan Konstruktivisme dalam Pembelajaran IPS - Afrilyanti; Desy Safitri; Sujarwo (PT. PENERBIT TIGA MUTIARA, 2024)
This research aims to discuss the importance of learning as a process that involves direct experience and not just remembering information. Researchers use a constructivist approach in social studies learning to see how students are engaged and their learning outcomes. Constructivism emphasizes the importance of a learning environment that can support students in developing their own perspectives. Through qualitative research methods with the type of library research, this research focuses on how to implement social studies learning using a constructivist approach because the challenges and teaching of social studies are often associated with still using traditional learning which tends to be monotonous and does not encourage student involvement. The research results show that the constructivist approach can actually provide social studies teachers with access to choose appropriate learning rules, provide opportunities to make their own assessments and of course can reduce the teacher's burden because the teacher only acts as a facilitator.